Reliability and Factor Structure of the Sex Offender Treatment Intervention and Progress Scale - Miner, Michael H.; Brouillette-Alarie, Sébastien; Davies, Simon T.; Newstrom, Nicholas; Robinson, Beatrice “Bean” E.; Thornton, David; Hanson, R Karl (Sexual abuse, 2023)
Assessment of risk of sexual recidivism has progressed from tools containing only static factors to tools including dynamic (i.e., changeable) risk factors. The psychometric properties and factor structure of one such scale, the Sex Offender Treatment Intervention and Progress Scale (SOTIPS) were explored. Seven hundred and thirty-one men assigned probation for sexual crimes in New York City and Maricopa County, Arizona were administered SOTIPS three times: intake into probation, six months later, and six months after that. SOTIPS showed good internal consistency (Time 1 ω = .87, Time 2 ω = .89, and Time 3 ω = .91), and acceptable inter-rater reliability (for the 26 cases rated in the same month, ICC =.821). An exploratory factor analysis did not result in the original factor structure proposed by the developers; instead, SOTIPS showed two factors: sexual risk and antisocial opposition. This factor structure required the averaging of two items to avoid collinearity. SOTIPS showed temporal invariance indicating that its factor structure and its association to underlying latent variables are consistent over time.